System for Observing and Recording School Buses in Real Time - V. , Deepak; T. , Gokul; B. , Niteesh; R. , Manish; V.D., Ambeth Kumar; A. , Mohan Vamsi (International Journal of Psychosocial Rehabilitation, 2020)
Day-by-day tracking systems are much needed for the safety of students that can be monitored by the parents. Parents need not worry about that student traveling. By making software to track students by scanning their unique barcode while boarding/exiting the bus. Students will not be able to abscond from the college after scanning the barcode. In case the student absconds from the college, automatically a notification will be sent to the parents. Through this system, the parent will be able to receive alert messages to their present phone number even if the parent is offline. Similarly, while returning back to home. Sending vehicle information like location details, speed, and distance traveled. We can implement this software widely for tracking cabs, stolen vehicles, school buses, etc.